Survey of a snow petrel nesting site in a remote high mountain region to inform designation of an Antarctic Specially Protected Area - Rümmler, Marie-Charlott; Esefeld, Jan; Pfeifer, Christian; Mustafa, Osama (Frontiers in Conservation Science, 2024)
Despite the sensitivity of ecosystems in extreme conditions, only 0.029 % of the Antarctic continent is currently granted special protection as Antarctic Specially Protected Area (ASPA). Additionally, protected areas are unevenly distributed and unrepresentative of the biodiversity of Antarctica. The Antarctic Treaty Consultative Parties are thus striving to establish a more coherent network of protected areas. In this context, the Otto-von-Gruber-Gebirge was identified as an area highly worthy of protection due to its unique ecosystem including one of the largest snow petrel breeding sites, and relative pristine nature. However, in the process of designation, an update of knowledge, particularly of the population status of snow petrel in the area, was recognized to be needed. This study was aimed at estimating a population census of snow petrel breeding pairs in the Lake Untersee catchment, an important subarea of the potentially protected area. Investigations were severely limited by the remoteness and harsh conditions of the area, enabling only a short fieldwork period with limited resources. Thus, a combination of remote sensing and traditional methods was applied. We conducted a ground survey of a smaller reference area, including locating nest sites and assessing nest site characteristics. Snow petrels usually nest in the cavities of large boulders and we thus classified habitat suitability based on boulder presence. To do so, the study area was remotely surveyed by unpiloted aerial vehicles to gain orthophotomosaics in sufficient resolution to distinguish on-ground conditions for breeding. We then calculated nest site densities for the reference area. Extrapolation from these densities to the whole study area gave us an estimated population of 11,765 breeding pairs. We also studied nest site data such as nest cavity depth, orientation, and attendance to gain basic knowledge of the characteristics of the breeding site. Finally, we measured a sample of four live snow petrels to determine which morph was present at the site. We were able to obtain nest site data and to extrapolate it, which produced population numbers of 11,765 breeding pairs for the whole study area. This underpins the size of the breeding site and thereby its importance for the species.